Costo de un ciclo de producción de maíz dulce y su incidencia en la rentabilidad de la finca niño Álvaro, parroquia San Carlos, cantón Quevedo año 2015 - Carbo Laje, Rosa Angélica (2015)
Once the investigation of the problem was accomplished, it is proceeded to recommend alternatives of solution. The used methodology answers to the requirements of the scientific investigation of knowledge, basing in the bibliographic revision, the main obtained results have relation with the objectives and operation the same that have been analyzed and interpreted even coming to the checking of the investigating study comes true with a view to indicate the methodologies that they enabled to verify the production costs in front of the benefit of the same, in order that the accounting process come true in the best way and not exist prostitutes in the future. Investigation came true with the aim of evaluating if a satisfactory profitability provides the aforementioned production when intervening producer verifies an adequate analysis that they enabled the costs in front of the benefit of the same, in order that the accounting process come true in the best way and not exist prostitute in the future.